ECONOMICS OF WATERSHED MANAGEMENT SANS BENEFITS FROM IRRIGATION IN SHIVALIK FOOT HILL VILLAGES - Agnihotri, Y.; Mittal, S.P.; Arya, Swarn Lata (Journal of Soil and Water Conservation, 2022)
The watershed management programmes on integrated basis have come to stay in Shivalik foothill region of northern India because of the multiple benefits derived from it. Rainwater harvesting and recycling for increasing and stabilizing agricultural productivity is the most crucial part of the programme as it leads to spectacular rise in socio-economic condition of the local people. However, water resource development is not feasible under all the situations. An attempt was therefore made to find out economic viability of watershed management programme without the water harvesting and irrigation component. The study revealed that in villages Behdala and Chattara where soil conservation works and catchment treatment were done at a cost of Rs. 5. 13 lakhs in 1984-85, spectacular increase (S0%) in yields of principal crops like maize and wheat was realized The increase in crop yields was due to a package comprising increased use of fertilizer, use of imporved seeds of varieties, and land levelling and land shaping and addition in number of improved farm implements. Gross returns worth Rs. 20 lakhs were obtained from crop yield in 1988-89 as against Rs. 15 lakhs before the project. As a result of increased availability of fodder both from agricultural fields and hilly areas, there was significant increase in number of milch cattle, boosting the milk yield by 77% over the pre-project period The gross returns from milk increased Rs. 15 lakhs. The benefit, cost ratio of the programme worked out to 1.67.